LINGUISTIC ANALYSIS ON JAVANESE LANGUAGE SELOGUDIG-AN DIALECT IN SELOGUDIG, PAJARAKAN, PROBOLINGGO - Lusi Nur Aini; Arining Wibowo; Maria G. Sri Ningsih (JURNAL ILMIAH BAHASA DAN SASTRA, 2015)
Linguistic analysis is an analysis of language study which include language form, language meaning, and language in context. Study of linguistic can learn the kind of approaches in language. For example, grammar, language and culture, like the study of cultural discourses and dialects is the domain of sociolinguistics, which looks at the relation between linguistic variation and social structures. Language is one of human characteristics because people living with language. Indonesia is well known of one thousand islands country and as 1000 languages country. So, in Indonesia, there are many vernaculars from each ethnicity in every region of Indonesia. Javanese language has the most speakers of the existing another language speakers. As a language that has a lot of speakers, Javanese language has a lot of kinds or dialect forms as a result of the space and time process. One of the examples is Selogudig-an language which is found in Probolinggo district, especially in Selogudig village, Pajarakan sub-district, Probolinggo district. From the linguistic aspects, Selogudig-an language is a dialect of the Javanese language. To analyze this research, the researcher used descriptive qualitative research design. It is intended to describe about how Javanese language Selogudig-an dialect is formed, the phonological, lexical and accent differences of Javanese language Selogudig-an dialect.